“Stenka Razin” by Prosper Mérimée: A commented translation of the third chapter - T. N. Goncharova (Шаги, 2024)
The historical essay “Stenka Razin” by Prosper Mérimée (first published in 1861) has never been translated into Russian. It was long considered an abridged translation into French of N. I. Kostomarov’s monograph The Revolt of Stenka Razin (1858). Yet, comparing both texts, one must recognize the real historical and literary originality of the French writer. Unlike Kostomarov, who gives a broad picture of a popular revolt, Mérimée’s narrative is centered on the figure of the Cossack ataman. The fragment translated here, based on the French edition of 1865, is the third chapter of the essay. It tells of the Persian campaign of the “raiding Cossacks” (1668–1669), followed by their triumphant return to the Don with rich booty. The central part of this chapter deals with the legend of the captive Persian princess, whom Razin allegedly threw into the waters of the Volga River. Mérimée, following Kostomarov, provides various explanations for this cruel action by the ataman, which looks senseless only at first glance. The successful outcome of the Cossack robber raids, as well as the generosity of the dashing ataman, contributed to the growth of his authority among the poor, and attracted more and more supporters to his army. In general, the events described in the third chapter appear as preparation for the culminating stage of the Razin movement, which occurred in 1670–1671.